Effectiveness of Acceptance and Commitment Therapy (ACT) on aggression of patients with psychosis due to methamphetamine use: A pilot study. (4th July 2018) - Ghouchani, Shaahin; Molavi, Nader; Massah, Omid; Sadeghi, Mandana; Mousavi, Seyed Hadi; Noroozi, Mehdi; Sabri, Armin; Farhoudian, Ali
ABSTRACT: Background and purpose: The aim of the current study was to evaluate the effectiveness of Acceptance and Commitment Therapy (ACT) on aggression and general health of patients with a diagnosis of psychosis due to methamphetamine use. Materials and Methods: This pilot study is an experimental controlled study with repeat measurements. Thirty patients were randomly assigned to study and control groups. The study group, received six weekly sessions of ACT, in addition to the usual treatment, while the control group received only the usual treatment. Both groups were tested using the General Health Questionnaire (GHQ-28) and Buss Perry Aggression Questionnaire (BPAQ) at three cross sections of time. Results: General health was improved significantly in study group comparing with control group (P < 0.0001). There were significant differences between the three time points of therapy (p = 0.0001; F(2, 56) = 41/456). Additionally, there were significant differences between the means of the three time points of therapy in aggressiveness variable (p = 0.0001; F(2, 56) = 190/845). Findings: ACT improved general health and decreased aggressiveness in the study group compared to the control group and may be a good therapy for methamphetamine dependents who suffer from psychosis.